Implementing the C.O.S.T.A Municipal Change Model (M-C-M) - Costa, King; Siganga, Selina (My University, 2020)
Corruption, mismanagement and incompetence are perceived as a significant prevention to great administration in progressive local government. Many attempts have been developed by government to curb the scourge of this problem by establishment of a number of public sector organizations hinged upon precepts of the constitution, such as Chapter 9 institutions. Regardless of so many watch-dog organizations in South Africa, it is obvious that these instruments are lacking to forestall and control debasement, because of helpless administration rehearses, for example, shortcoming and "holes" in practice. Moreover, the government and public sector continually see exposition of lack of ethical leadership, ethical administration and ethical public service as a result. Apparent refusal to follow the statutory prescripts in the form of PFMA and MFMA demonstrate a plethora of unending meanders to total decay and maleficence. According to Naidoo (2010) Administration and service delivery failures by local government can generally be ascribed to : (1) Poor leadership (2) Unrealistic planning (3) Lack of proper community engagement (4) Trust deficit (5) Incompetent staff and management It is interesting that issues raised over a decade ago, which were already proving a predominant challenge to service delivery, are still a problem 10 years later and over 25 years of democratic rule in South Africa. In 2010, Naidoo's study collected data from households, which indicated that appointment of officials to office was inappropriate and irregular. This was further compounded by low skills levels and non-responsive employee capacity development suitable to the paradigm of local government. It is in this way contended there is progressively a requirement for moral authority and ethical leadership culture in the public service and local government. This article hence recommends the requirement for a framework that will put local government leadership and staff on a trajectory with sequential development indicators providing verification at each stage. The C.O.S.T.A. Framework is hereby proposed.
Keywords: Change; Concepts; Local Government; Methods; Problem-Solving; Strategy